Fall‐Associated Difficulty with Activities of Daily Living in Functionally Independent Individuals Aged 65 to 69 in the United States: A Cohort Study. Issue 1 (11th January 2013) - Sekaran, Nishant K.; Choi, Hwajung; Hayward, Rodney A.; Langa, Kenneth M.
<x xml:space="preserve">Abstract</x> Objectives To determine whether falling would be a marker for future difficulty with activities of daily (ADLs) that would vary according to fall frequency and associated injury. Design Longitudinal analysis. Setting Community. Participants Nationally representative cohort of 2, 020 community‐living, functionally independent older adults aged 65 to 69 at baseline followed from 1998 to 2008. Measurements ADL difficulty. Results Experiencing one fall with injury (odds ratio (OR) = 1.78, 95% confidence interval (CI) = 1.29–2.48), at least two falls without injury (OR = 2.36, 95% CI = 1.80–3.09), or at least two falls with at least one injury (OR = 3.75, 95% CI = 2.55–5.53) in the prior 2 years was independently associated with higher rates of ADL difficulty after adjustment for sociodemographic, behavioral, and clinical covariates. Conclusion Falling is an important marker for future ADL difficulty in younger, functionally independent older adults. Individuals who fall frequently or report injury are at highest risk.